Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1139/cjas-2019-0101
|View full text |Cite
|
Sign up to set email alerts
|

The use of artificial neural networks for modelling rumen fill

Abstract: Artificial Neural Network (ANN) and Random Forest models for predicting rumen fill of cattle and sheep were developed. Data on rumen fill were collected from studies that reported body weights, measured rumen fill and stated diets fed to animals. Animal and feed factors that affected rumen fill were identified from each study and used to create a dataset. These factors were used as input variables for predicting the weight of rumen fill. For ANN modelling, a three-layer Levenberg-Marquardt Back Propagation Neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Several studies have compared the performance of traditional predictive tools (i.e., multiple linear regression and random forest) versus ANN to estimate milk yield 15 , 21 , predict mastitis 27 , forecasting cow locomotion score 28 , prediction of body weight 29 , 30 , modelling rumen fill 31 and prediction of carcass tissue composition 32 . Compared with MLR, results from the current study revealed a better performance of ANN to estimate milk yield based on udder measures.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have compared the performance of traditional predictive tools (i.e., multiple linear regression and random forest) versus ANN to estimate milk yield 15 , 21 , predict mastitis 27 , forecasting cow locomotion score 28 , prediction of body weight 29 , 30 , modelling rumen fill 31 and prediction of carcass tissue composition 32 . Compared with MLR, results from the current study revealed a better performance of ANN to estimate milk yield based on udder measures.…”
Section: Discussionmentioning
confidence: 99%